If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(-15) = -7 Multiply -1 * -15 x + 15 = -7 Reorder the terms: 15 + x = -7 Solving 15 + x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + x = -7 + -15 Combine like terms: 15 + -15 = 0 0 + x = -7 + -15 x = -7 + -15 Combine like terms: -7 + -15 = -22 x = -22 Simplifying x = -22
| 10x^2-3x-27=0 | | 35x^2=19x-2 | | 2(5h+1)=10h+4 | | =14xz-18xz^2 | | 5y=3x-10 | | 8x^2+6x-5=0 | | -6=16+x | | 8x^2+56p=-98 | | 144+100y^2= | | (x+5)(x-3)x=2 | | 3y=9x-12 | | P^5=9P^4 | | (x+5)(x-39)x=2 | | 6x^3+5x^2-9x+2=0 | | 4=-2(x+5)+8x | | 5(x+3)-(5x+15)=0 | | 15x+20(x-3)=325 | | -36-9x+4x^2+3x=0 | | 64y^2=25 | | (3a-3)(4a-5)= | | 5(4+c)=4(c-4) | | y+x=3 | | 3y-2(18)=3 | | 5-4x=19+3x | | -4n+13=-3n-10 | | -2Y-12=5Y+30 | | 5Y-7=2Y+2 | | -7(5v-u-3)= | | (6x^2-16x+33)=0 | | (5w-15)(15w-5)=0 | | -4+15=14x-3-13x | | 4(8-w)= |